MASS MEDIA IN UZBEKISTAN - Sotvoldiyeva Mohlaroyim Ulugʻbek qizi; To'htamirzayeva Robiyaxon (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Mass media in Uzbekistan is concerned with the situation of Uzbek media. Although a government decree officially eliminated state censorship in 2002, it has continued to severely restrict independent journalism, particularly following the Andijon uprising of 2005. Licensing and regulation are the purview of the State Press Committee and the Inter-Agency Coordination Committee, which use their authority to harass and delay the activities of independent media outlets.